A Recently Formed Triploid Cardamine insueta Inherits Leaf Vivipary and Submergence Tolerance Traits of Parents - Sun, Jianqiang; Shimizu-Inatsugi, Rie; Hofhuis, Hugo; Shimizu, Kentaro; Hay, Angela; Shimizu, Kentaro K.; Sese, Jun (Frontiers in Genetics, 2020)
Contemporary speciation provides a unique opportunity to directly observe the traits and environmental responses of a new species. Cardamine insueta is an allotriploid species that appeared within the past 150 years in a Swiss village, Urnerboden. In contrast to its two progenitor species, C. amara and C. rivularis that live in wet and open habitats, respectively, C. insueta is found in-between their habitats with temporal water level fluctuation. This triploid species propagates clonally and serves as a triploid bridge to form higher ploidy species. Although niche separation is observed in field studies, the mechanisms underlying the environmental robustness of C. insueta are not clear. To characterize responses to a fluctuating environment, we performed a time-course analysis of homeolog gene expression in C. insueta in response to submergence treatment. For this purpose, the two parental (C. amara and C. rivularis) genome sequences were assembled with a reference-guided approach, and homeolog-specific gene expression was quantified by using HomeoRoq software. We found that C. insueta and C. rivularis initiated vegetative propagation by forming ectopic meristems on leaves, while C. amara did not. We examined homeolog-specific gene expression of three species at nine time points during the treatment. The genome-wide expression ratio of homeolog pairs was 2:1 over the time-course, consistent with the ploidy number. By searching the genes with high coefficient of variation of expression over time-course transcriptome data, we found many known key transcriptional factors related to meristem development and formation upregulated in both C. rivularis and rivularis-homeolog of C. insueta, but not in C. amara. Moreover, some amara-homeologs of these genes were also upregulated in the triploid, suggesting trans-regulation. In turn, Gene Ontology analysis suggested that the expression pattern of submergence tolerant genes in the triploid was inherited from C. amara. These results suggest that the triploid C. insueta combined advantageous patterns of parental transcriptomes to contribute to its establishment in a new niche along a water-usage gradient.